2021
DOI: 10.1109/tii.2020.3014401
|View full text |Cite
|
Sign up to set email alerts
|

Fault-Tolerant Multisubset Aggregation Scheme for Smart Grid

Abstract: As smart cities and nations are fast becoming a reality, so does the underpinning infrastructure such as smart grids. One particular challenge associated with smart grid implementation is the need to ensure privacy preserving multisubset data aggregation. Existing approaches generally require the collaboration of a trusted third party (TTP), which may not be practical. This also increases the threat exposure, as the attacker can now target the TTP who may be servicing several smart grid operators. Therefore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 29 publications
(43 reference statements)
1
70
0
Order By: Relevance
“…Besides, we will try to compare more algorithms, such as jSO [138], LSHADESPACMA [139], EAGDE [140], and EBLSHADE [141]. The problems that can benefit from applying the AGOA are not limited to parameter optimization [142], deployment optimization in node arrangement in the sensor networks [143], or finding the optimal solutions for resource allocation [144]; potential areas in which the proposed GOA-based cores can be used include landslide prediction [145], environmental cases that need cross-optimization [146], [147], target tracking systems that need high accuracy and consistency [148], development of efficient hydrothermal systems [47], development and equipment tracking systems [149], decision making and management of supply chains [150], industrial problems such as the development of the order-picking systems [151], applications in image enhancement [152], smart agriculture [153], and smart grids [154]. Other problems, including social manufacturing optimization [155] and video coding optimization [156], are also exciting topics worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we will try to compare more algorithms, such as jSO [138], LSHADESPACMA [139], EAGDE [140], and EBLSHADE [141]. The problems that can benefit from applying the AGOA are not limited to parameter optimization [142], deployment optimization in node arrangement in the sensor networks [143], or finding the optimal solutions for resource allocation [144]; potential areas in which the proposed GOA-based cores can be used include landslide prediction [145], environmental cases that need cross-optimization [146], [147], target tracking systems that need high accuracy and consistency [148], development of efficient hydrothermal systems [47], development and equipment tracking systems [149], decision making and management of supply chains [150], industrial problems such as the development of the order-picking systems [151], applications in image enhancement [152], smart agriculture [153], and smart grids [154]. Other problems, including social manufacturing optimization [155] and video coding optimization [156], are also exciting topics worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In [65], the authors investigated the Korean campus to find the viability of microgrid implementation especially investors. e payback period revealed that the initial cost will cover within a few years and shifted the conventional system into a smart [66][67][68] power system. In [69], the authors analyzed a large number of customers in the US region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the actual situation, the finite element method is adopted and ANSYS software is used to simulate and solve the ground potential distribution [20,21]. e field circuit coupling method is usually used to calculate DC bias of the main transformer in the urban area.…”
Section: Integrated Model Of "Stray Current-geoelectric Field-magnetic Bias Dc"mentioning
confidence: 99%